Mapping of the ribosomal RNA genes on spinach chloroplast DNA. - Whitfeld, P R (1978)
Spinach chloroplast ribosomal RNAs have been hybridized to restriction endonuclease fragments of spinach chloroplast DNA. All three RNA species (23S, 16S and 5S) hybridized to a single large fragment when the DNA was digested with either Sall or Pstl. Hybridization of 23S RNA to fragments produced by Smal yielded two radioactive bands which corresponded to the bi-molar 2.5 X 10(6) and 1.15 X 10(6) Mr fragments. 16S RNA also hybridized to two, bi-molar Smal fragments (3.4 X 10(6) and 2.5 X 10(6) Mr) and 5S RNA hybridized to the 1.15 X 10(6) Mr bi-molar Smal fragment. The 23S RNA and 16S RNA cistrons were each also shown to contain a single EcoRI site. From the data it was possible to conclude that the ribosomal RNA genes are located on the inverted repeat region of the spinach chloroplast DNA restriction map [1,2], that the sequence of the cistrons is 16S - 23S - 5S and that the size of the spacer between the 16S and 23S RNA cistrons is approximately 0.90 X 10(6) Mr.